"We will be the last mass shooting": Emma González's tactical subjectivity through differential consciousness, affect, and silence - Palomino, Selena J., author; Aoki, Eric, advisor; Khrebtan-Hörhager, Julia, committee member; Black, Ray, committee member (Colorado State University. Libraries, 2019)
The purpose of this thesis is to uncover the rhetorical strategies employed by Emma González throughout her "We call BS!" speech (i.e., February 17, 2018) and her "March for Our Lives" speech (i.e., March 24, 2018). Chela Sandoval's theorization of differential consciousness is used to uncover the ways González shifts her subject position from "kid," "teenager," and "student" in order to challenge "adults," the "President," and "lawmakers" to create systemic change. In this thesis, I argue Emma González uses the affective capacities of grief and silence to construct a counterpublic. Through González's rhetorical strategies a moment of silence is transformed from a ritual to a political act. Public grief is used as a tool for healing and reconciliation allowing for a national community to contend with the harrowing effects of gun violence. To conclude, with gun violence continuing to be a pervasive social problem, I discuss contributions, limitations, and directions for future studies.
We will be the last mass shooting: Emma González's tactical subjectivity through differential consciousness, affect, and silence